2020
DOI: 10.54203/scil.2020.wvj68
|View full text |Cite
|
Sign up to set email alerts
|

Canine Parvovirus Infection in Dogs: Prevalence and Associated Risk Factors in Egypt

Abstract: Canine parvovirus (CPV) infection is a global infectious and contagious viral disease of canine, especially in dogs infected by three variants of CPV type. This study aimed to investigate the prevalence and potential risk factors of parvovirus infection in dogs residing in Egypt. A total of 122 dogs suffering from vomiting and diarrhea were screened by antigen rapid CPV/Canine Coronavirus Ag test kit for the diagnosis of CPV infection from March 2012 to February 2013. Age, breed, season, and vaccination of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…The variation in the prevalence of CPV might be attributed to varied diagnostic tests, wide variation in the number of samples, differences in study period, geographical area variations; thus, comparison in this regard would be less beneficial (Khare et al, 2019) [13] . Breed wise, prevalence of CPV infection were found to be maximum in mongrels i.e., 51.16% (132/258), which is in accordance with findings by Behera et al, (2015) [6] and Sayed-Ahmed et al, (2021) [27] who reported 34.48% and 48.5% respectively which might be due to higher density of mongrels in the study area, they are inherently of wandering nature; close proximity to each other increases the chances of infection spread; due to lack of awareness and responsibility, vaccination schedules are not rightly followed by mongrel dog owners thus pre-disposing them to the disease (Behera et al, 2015) [6] (Table 2) (Figure 2). As of exotic breeds, Labrador retriever showed the highest prevalence rate (9.68%), followed by German Shepherd (8.53%) and Rottweiler (8.14%) respectively which is concurrent with findings of Behera et al, (2015) [6] (Table2) (Figure2).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The variation in the prevalence of CPV might be attributed to varied diagnostic tests, wide variation in the number of samples, differences in study period, geographical area variations; thus, comparison in this regard would be less beneficial (Khare et al, 2019) [13] . Breed wise, prevalence of CPV infection were found to be maximum in mongrels i.e., 51.16% (132/258), which is in accordance with findings by Behera et al, (2015) [6] and Sayed-Ahmed et al, (2021) [27] who reported 34.48% and 48.5% respectively which might be due to higher density of mongrels in the study area, they are inherently of wandering nature; close proximity to each other increases the chances of infection spread; due to lack of awareness and responsibility, vaccination schedules are not rightly followed by mongrel dog owners thus pre-disposing them to the disease (Behera et al, 2015) [6] (Table 2) (Figure 2). As of exotic breeds, Labrador retriever showed the highest prevalence rate (9.68%), followed by German Shepherd (8.53%) and Rottweiler (8.14%) respectively which is concurrent with findings of Behera et al, (2015) [6] (Table2) (Figure2).…”
Section: Resultssupporting
confidence: 90%
“…Also, after 3 months of age, a decline in maternal antibody titres predisposes the age group of 3-6 months to CPV infection and increases susceptibility to infection in endemic areas due to lack of protective titres (O'Brien, 1994; Deka et al, 2013) [21,7] . Sex wise prevalence of CPV infection was found to be more in males (63.57%) compared to females (34.43%) which are supported by the findings of Sagare et al, (2022) [25] ; Singh et al, (2021) [34] and Sayed-Ahmed et al, (2021) [27] respectively (Table 2) (Figure 4). In contrast, Banja et al, (2002) [3] and Sanjukta et al, (2011) [26] in respective studies reported that no significant difference was observed among sexes of dogs with CPV infection as there was no influence of sex on the incidence of CPV infection.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The clinical findings encountered matches well with the findings of [7,10,12] who found presence of anorexia, vomition, bloody diarrhoea, moderate to severe dehydration, restlessness among the dogs affected with parvovirus infection. Various clinical findings in dogs affected with parvovirus shows changes in their frequency of appearance depending on the level of damage the virus causes within the body.…”
Section: Discussionsupporting
confidence: 88%